Penerapan Konsep Himpunan Dominasi pada Teori Graf untuk Optimalisasi Jumlah Kebocoran Pipa Air Minum di Desa Mausamang, Kabupaten Alor - Landerius Maro; Orpa Herlovina Yoplib (Fakultas Pertanian, Universitas Timor, 2021)
Regional development is one of the problems that are often faced by PDAM. The development of the area is the development of a water pipe distribution network. The more people there are, the more people will find it difficult to get optimal drinking water because they leak it without thinking about other peoples. As an example of the problem of regional development, there are several areas that have not received water from PDAM, this shows that the distribution of clean water isn’t optimal. In an effort to overcome these problems, an action is needed to optimize the pipe leaks. The purpose of this study is to minimize the leaks of the primary pipe by using the concept of applying the domination set of graph theory. The research steps carried out by researchers include data collection, determining the domination set, and distribution of drinking water pipelines. The comparison of the total initial primary pipe leaks points is 80 points that dominate 117 house points and by minimizing the primary pipe leaks by applying the concept of the domination set to 44 points that dominate 117 house points there is a reduction of 36 primary pipe leaks points that will be closed. The data concludes that the concept of the domination set on the graph can be used to find the optimal network in the PDAM water distribution network.